Synthesis, characterization and environmental application of silica grafted photoactive substances isolated from urban biowaste. Issue 59 (28th June 2015) - Testa, Maria Luisa; Tummino, Maria Laura; Agostini, Silvia; Avetta, Paola; Deganello, Francesca; Montoneri, Enzo; Magnacca, Giuliana; Prevot, Alessandra Bianco
<x xml:space="preserve">Abstract</x> Hybrid biowaste-derived silica-based systems show good photoactive performance, stability and reusability in the degradation of water pollutants.